Comparing the Effectiveness of Emotion Regulation and Logotherapy on the Quality of Life in Adolescents with Anxiety Disorders - Marzieh Sadat Seyed Ghandi; Hayedeh Saberi; Malek Mirhashmi (Iranian Journal of Educational Research)
Objective: The current investigation was undertaken with the objective of evaluating the comparative efficacy of emotion regulation strategies and logotherapy on the enhancement of quality of life among adolescents diagnosed with anxiety disorders. Methods: The methodology employed in this study was a semi-experimental design comprising a pre-test and post-test framework, inclusive of a control group. To facilitate data collection, the Quality of Life Questionnaire and the Child and Adolescent Anxiety Disorders Questionnaire were utilized. Furthermore, the emotion regulation intervention was implemented using a structured emotion regulation package derived from the theoretical framework posited by Garnefski and Kraaij alongside a logotherapy package grounded in Frankl's theoretical constructs. Data analysis was executed utilizing SPSS version 22 software at a significance threshold of 0.05, employing mixed covariance analysis. Results: The findings indicated that the quality of life metrics for the experimental groups exhibited a statistically significant enhancement from pre-test to post-test, with this improvement being sustained during the follow-up evaluation period. Additionally, the outcomes derived from the post hoc analysis revealed that the mean quality of life scores across all paired group comparisons did not demonstrate any statistically significant differences; in other words, no noteworthy distinction was identified between emotion regulation and semantic therapy concerning the quality of life variable. Conclusions: The results obtained lend credence to the efficacy of emotion-focused therapeutic interventions as well as those employing a existential framework.